Establishment of a reverse transcription real-time quantitative PCR method for Getah virus detection and its application for epidemiological investigation in Shandong, China - Cao, Xinyu; Qiu, Xiangshu; Shi, Ning; Ha, Zhuo; Zhang, He; Xie, Yubiao; Wang, Peng; Zhu, Xiangyu; Zhao, Wenxin; Zhao, Guanyu; Jin, Ningyi; Lu, Huijun (Frontiers in Microbiology, 2022)
Getah virus (GETV) is a mosquito-borne, single-stranded, positive-sense RNA virus belonging to the genus Alphavirus of the family Togaviridae. Natural infections of GETV have been identified in a variety of vertebrate species, with pathogenicity mainly in swine, horses, bovines, and foxes. The increasing spectrum of infection and the characteristic causing abortions in pregnant animals pose a serious threat to public health and the livestock economy. Therefore, there is an urgent need to establish a method that can be used for epidemiological investigation in multiple animals. In this study, a real-time reverse transcription fluorescent quantitative PCR (RT-qPCR) method combined with plaque assay was established for GETV with specific primers designed for the highly conserved region of GETV Nsp1 gene. The results showed that after optimizing the condition of RT-qPCR reaction, the minimum detection limit of the assay established in this study was 7.73 PFU/mL, and there was a good linear relationship between viral load and Cq value with a correlation coefficient (R2) of 0.998. Moreover, the method has good specificity, sensitivity and repeatability. The established RT-qPCR is 100-fold more sensitive than the conventional RT-PCR. The best cutoff value for the method was determined to be 37.59 by receiver operating characteristic (ROC) curve analysis. The area under the curve (AUC) was 0.956. Meanwhile, we collected 2847 serum specimens from swine, horses, bovines, sheep and 17080 mosquito specimens in Shandong Province in 2022. The positive detection rates by RT-qPCR were 1%, 1%, 0.2%, 0% and 3% respectively. In conclusion, the method was used for epidemiological investigation, which has extensive application prospects.